Beyond Classical Coordination Chemistry: The First Case of a Triply Bridging Phosphine Ligand. Issue 22 (22nd April 2021) - Baranov, Andrey Y.; Pritchina, Elena A.; Berezin, Alexey S.; Samsonenko, Denis G.; Fedin, Vladimir P.; Belogorlova, Nataliya A.; Gritsan, Nina P.; Artem'ev, Alexander V.
Abstract: The first example of a triply bridging (μ3 ‐P) phosphine ligand has been discovered in the crown‐shaped [Cu3 (μ2 ‐Hal)3 L] (Hal=Cl, Br, or I) complexes supported by tris[2‐(2‐pyridyl)ethyl]phosphine (L). Theoretical analysis completely confirms the observed μ3 ‐P‐bridging pattern, revealing the interaction of the same lone pair of phosphorus with three valence 4s‐orbitals of Cu atoms. The presented complexes exhibit outstanding blue phosphorescence ( λ em =442–465 nm) with the quantum efficiency reaching 100 %. The complex [Cu3 (μ2 ‐I)3 L] also exhibits remarkable thermo‐ and mechanochromic luminescence resulting in a sharp change in the emission colour upon external stimuli. These findings essentially contribute to coordination chemistry of the pnictine ligands. Abstract : Phosphines are notorious in acting exclusively as terminal donors, binding a single metal center. We have discovered that a non‐traditional scenario is possible where the phosphorus(III) atom of a R3 P ligand bridges three metal atoms at once. Such triply bridging pattern is first observed in the [Cu3 (μ2 ‐Hal)3 L] (Hal=Cl, Br, or I) complexes, which also exhibit remarkable luminescence properties.